Approximate Controllability of Fractional Nonlinear Hybrid Differential Systems via Resolvent Operators. (25th March 2019) - Matar, Mohammed M.
Abstract : We obtain sufficient conditions for the approximate controllability of a fractional nonlinear hybrid differential system. The results are obtained by using resolvent and sectorial operators technique via Dhage fixed point theorem.